If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5m + -27 = 48 Reorder the terms: -27 + 5m = 48 Solving -27 + 5m = 48 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '27' to each side of the equation. -27 + 27 + 5m = 48 + 27 Combine like terms: -27 + 27 = 0 0 + 5m = 48 + 27 5m = 48 + 27 Combine like terms: 48 + 27 = 75 5m = 75 Divide each side by '5'. m = 15 Simplifying m = 15
| (X+3)(x-4)=7 | | 12x+3-3=12x | | 5p^2+33p+40=0 | | 10n+3=313 | | (3x-4)^2/5=6 | | 7/4r=29/8 | | 6y+6x=5y | | 5/y-2/y=-4 | | 8y+12=52 | | -5/2/-1/2-x | | 4y^2=x^2-4 | | P-626/14=25 | | x+2x-5=4x-6 | | 97=12n | | 7/8×50×9/11×15 | | 0=5x^2-x | | -3/-5=7 | | 3x^2+19x+13=0 | | y=x-x+y | | 7=7y+4(y+7) | | 6m^2-26=-m | | 6y+6x=5y+2x | | 4[2t-4]= | | y-1=-7(x+4) | | 12-8t=-52 | | y-2=.16666(x-6) | | -5-2m=9 | | 7(6m-6)+3=-81 | | 8t-16= | | 2x+8=14x+12 | | y=t+t-y | | 3(-40+-2r)+20= |